TINGKAT KEPATUHAN PENGOBATAN HIPERTENSI PADA PASIEN PROLANIS DI PUSKESMAS CISARUNI KABUPATEN TASIKMALAYA: Medication Adherence Level of Hypertensive Patients in the Prolanis Program at Cisaruni Community Health Center Tasikmalaya District - Nofianti, Tita; Arman, Siti Alisa; Sutaryat, Lulu Dhamayanti; Rahayuningsih, Nur; Lestari, Tresna (JFL : Jurnal Farmasi Lampung, 2025)
Hypertension is a chronic disease requiring long-term management and high adherence to drug therapy. The Chronic Disease Management Program (Prolanis) at Cisaruni Community Health Center aims to improve the quality of life of hypertensive patients through treatment monitoring. This study used a quantitative descriptive approach with a cross-sectional design involving 60 Prolanis hypertensive patients. Data were collected through interviews using the validated Morisky Medication Adherence Scale-8 (MMAS-8) questionnaire. The results showed that 21.7% of patients had high adherence, 48.3% had moderate adherence, and 30% had low adherence, with an average score of 6.62, indicating moderate adherence. These findings suggest that the majority of patients are not fully adherent to antihypertensive therapy. Factors such as age, education level, and duration of hypertension are suspected to influence adherence. Educational interventions, improved healthcare worker-patient communication, and family involvement are needed to enhance medication adherence.   Keywords:  Cisaruni Community Health Center, Hypertension, Medication Adherence, MMAS-8,  Prolanis